2017
DOI: 10.3390/ijgi6050147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Resolution Topographic Mapping on Beach Morphological Analyses Based on Terrestrial LiDAR and Object-Oriented Beach Evolution

Abstract: This research applied terrestrial LiDAR for laboratory beach evolution experiments to quantify the impact of resolution on topographic mapping and change analyses. The multi-site registration and multi-temporal scanning processes produced high accuracy (−0.002 ± 0.003 m) topographic models in a wave tank environment. Morphological analyses based on surface change and profiles showed that models of all resolutions were capable of capturing major sediment changes in relatively smooth areas. However, higher resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Through tracking the time where a pulse occurred in a laser beam, as trigged by an object, LiDAR technology can measure the location of the object and, hence, produces dense point clouds with X, Y, and Z coordinates for objects on or above the ground surface. The derived raw LiDAR point clouds from the multi-site scanning of typical coastal landscapes are a mixture of measurements from the ground, marshes, birds and boats, and from artificial facilities such as floating buoys and buildings, as well as other harbor infrastructure [19,26,38]. To generate DEM from these dense point surveys, points reflected from the ground surface need to be filtered first and then interpolated into 3-D terrain models of the terrain [39].…”
Section: Stage 1: Initial Dem Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through tracking the time where a pulse occurred in a laser beam, as trigged by an object, LiDAR technology can measure the location of the object and, hence, produces dense point clouds with X, Y, and Z coordinates for objects on or above the ground surface. The derived raw LiDAR point clouds from the multi-site scanning of typical coastal landscapes are a mixture of measurements from the ground, marshes, birds and boats, and from artificial facilities such as floating buoys and buildings, as well as other harbor infrastructure [19,26,38]. To generate DEM from these dense point surveys, points reflected from the ground surface need to be filtered first and then interpolated into 3-D terrain models of the terrain [39].…”
Section: Stage 1: Initial Dem Generationmentioning
confidence: 99%
“…Among the new remote sensing technologies, terrestrial LiDAR has demonstrated significant advantages for quick and accurate 3D topographical mapping [26], and started to fill the gap between satellite-based remotely sensed mapping and tedious point-based field surveys. Terrestrial LiDAR, also called terrestrial laser scanning, is a portable surveying system mounted on a tripod that can rotate 360 degrees to acquire virtual realitylike color-coded dense point clouds of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, beach topographic data is obtainable using a variety of ground-based (graded rods 16 , surveyor-grade global positioning systems or total stations 17 , terrestrial LiDAR 18 ) or aerial-based (airborne LiDAR 19 , traditional photogrammetry 20 , 21 , unmanned aerial vehicles 22 , 23 ) approaches. While ground-based surveying methods are labour intensive and of limited spatial coverage, airborne LiDAR or traditional photogrammetric approaches are cost-prohibitive for monitoring purposes, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies among the data or seasonal and annual landscape changes can introduce significant errors in the ever-changing coastal environments affected by hydrodynamics, hazards, and human activities. Furthermore, LiDAR boasts the best for high-resolution terrain mapping [18,19] among current mapping technologies, but the equipment is costly. Frequent deployment of airborne LiDAR for surveys is cost prohibitive, urging for affordable method for rapid and accurate measurements without relying on out-of-dated historical data [2,3].…”
Section: Introductionmentioning
confidence: 99%